Recycling of Iron Slag Waste in the Production of Ceramic Roof Tiles. (11th August 2022) - Ahmed, M. M.; El Naggar, K. A. M.; Abadir, M. F.; Abbas, W.; Hamid, E. M. Abdel
Abstract : The merit of this study is manufacturing cheaper roof tiles using fluxed waste material such as granulated iron slag, in addition to the environmental benefit of decreasing the cost and negative impact of their disposal and landfilling. Waste water-cooled granulated iron slag was ground and added in proportions ranging from 0 to 30 wt.% to kaolin clay to prepare roof tiles for the economic purpose of decreasing the production cost by incorporating cheap waste and to serve sustainability. The raw materials were characterized by XRD, XRF, and particle size analysis. The specimens were shaped using a rectangular mould with dimensions of 150 × 30 × 30 mm 3 under an axial pressure of 10 MPa and then dried in a dryer at 110°C. The firing of the dried specimens was carried out at 900, 1000, and 1100°C. The characteristics of fired specimens were determined by their linear firing shrinkage, water absorption, compressive strength, and freezing-thawing resistance. Results showed that samples containing 20% slag waste and fired at 1000°C displayed a cold water absorption of 12% and a saturation coefficient of 0.82, both values being lower than the maximum value recommended by standards. Also, the recorded breaking strength of 5040 N was much higher than the minimum standard value. These samples were also subjected to 50 freeze-thawing cycles, which they passed without the appearance of any cracks. It was concluded that samples containing 20% slag waste and fired to 1000°C or 1100°C fulfilled the requisites of ASTM C1167 for grade 3 normal duty roof tiles.